Pengaruh Akuntabilitas Pelayanan Terhadap Kepuasan Masyarakat Didalam Pelayanan Publik Di Kelurahan Waihaong Kota Ambon - Masnia, Masnia; Rahawarin, Mohamad A.; Waisapy, Jeanly (Jompa Research and Development, 2024)
Waihaong Village is one of the villages in Nusaniwe Subdistrict which is the spearhead of services to the community and is also referred to as a public service base. some of the problems encountered in the service section are that there are still complaints from the public about the service of making business certificates that are so convoluted and take a long time. This is because people who want to get services are less informed. Service is less satisfying in terms of employee friendliness to the community. This study aims to determine